Applications of Self-Assembled Monolayers in Surface-Enhanced Raman Scattering - Charles K. Klutse; Adam Mayer; Julia Wittkamper; Brian M. Cullum (Journal of Nanotechnology)
The increasing applications of surface-enhanced Raman scattering (SERS) has led to the development of various SERS-active platforms (SERS substrates) for SERS measurement. This work reviews the current optimization techniques available for improving the performance of some of these SERS substrates. The work particularly identifies self-assembled-monolayer- (SAM-) based substrate modification for optimum SERS activity and wider applications. An overview of SERS, SAM, and studies involving SAM-modified substrates is highlighted. The focus of the paper then shifts to the use of SAMs to improve analytical applications of SERS substrates by addressing issues including long-term stability, selectivity, reproducibility, and functionalization, and so forth. The paper elaborates on the use of SAMs to achieve optimum SERS enhancement. Specific examples are based on novel multilayered SERS substrates developed in the author’s laboratory where SAMs have been demonstrated as excellent dielectric spacers for improving SERS enhancement more than 20-fold relative to conventional single layer SERS substrates. Such substrate optimization can significantly improve the sensitivity of the SERS method for analyte detection.